Stroke Etiology and Thrombus Computed Tomography Characteristics in Patients With Acute Ischemic Stroke: A MR CLEAN Registry Substudy. Issue 6 (June 2020) - Boodt, Nikki; Compagne, Kars C.J.; Dutra, Bruna G.; Samuels, Noor; Tolhuisen, Manon L.; Alves, Heitor C.B.R.; Kappelhof, Manon; Lycklama à Nijeholt, Geert J.; Marquering, Henk. A.; Majoie, Charles B.L.M.; Lingsma, Hester F.; Dippel, Diederik W.J.; et al.
Abstract : Background and Purpose—: If a relationship between stroke etiology and thrombus computed tomography characteristics exists, assessing these characteristics in clinical practice could serve as a useful additional diagnostic tool for the identification of stroke subtype. Our purpose was to study the association of stroke etiology and thrombus computed tomography characteristics in patients with acute ischemic stroke due to a large vessel occlusion. Methods—: For 1429 consecutive patients enrolled in the MR CLEAN Registry, we determined stroke cause as defined by the TOAST (Trial of ORG 10172 in Acute Stroke Treatment) criteria. The association of stroke etiology with the hyperdense artery sign, clot burden score, and thrombus location was estimated with univariable and multivariable binary and ordinal logistic regression. Additionally, for 367 patients with available thin-section imaging, we assessed the association of stroke etiology with absolute and relative thrombus attenuation, distance from internal carotid artery-terminus to thrombus, thrombus length, and thrombus attenuation increase with univariable and multivariable linear regression. Results—: Compared with cardioembolic strokes, noncardioembolic strokes were associated with presence of hyperdense artery sign (odds ratio, 2.2 [95% CI, 1.6–3.0]), lower clot burden score (common odds ratio, 0.4 [95% CI, 0.3–0.6]), shift towards a more proximal thrombus location (common odds ratio, 0.2 [95% CI, 0.2–0.3]), higher absolute thrombus attenuation (β, 3.6 [95% CI, 0.9–6.4]), decrease in distance from the ICA-terminus (β, −5.7 [95% CI, −8.3 to −3.0]), and longer thrombi (β, 8.6 [95% CI, 6.5−10.7]), based on univariable analysis. Thrombus characteristics of strokes with undetermined cause were similar to those of cardioembolic strokes. Conclusions—: Thrombus computed tomography characteristics of cardioembolic stroke are distinct from those of noncardioembolic stroke. Additionally, our study supports the general hypothesis that many cryptogenic strokes have a cardioembolic cause. Further research should focus on the use of thrombus computed tomography characteristics as a diagnostic tool for stroke cause in clinical practice. Abstract : Supplemental Digital Content is available in the text.